2021
DOI: 10.1111/jfpp.15271
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chocolate fortification withCentella asiatica, Abelmoschus esculentus,andPsidium guajavaon the content of biologically active substances

Abstract: Herbal‐based chocolate consists of micro‐nutrients and spices, which can be consumed in infinite combinations. This research examines the combination of Centella asiatica, Abelmoschus esculentus, and Psidium guajava in the process of chocolate formulation. The concentration of the product was optimized based on taste, flavor, texture, and stability. The optimized concentration was subjected to Nutritional, Stability, Sensory, Anti‐oxidant, Antimicrobial, and shelf life analysis. The Nutritional analysis shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hence, Şahin‐Cebeci (2019) showed that incorporating 2% (w/w) Spirulina in homemade chocolate had nearly four times the protein content of commercial baby foods, and it could meet the required daily intake of essential amino acids, histidine, and arginine for infants and children. Raja et al (2021) increased the amount of physiologically active substances in chocolate by including Centella asiatica , Abelmoschus esculentus , and Psidium guajava in the formula compared to conventional chocolates, the optimized product contained more calcium (67.8 mg), iron (2.34 mg), and sodium (355 mg) per 100 g (13 mL of C. asiatica , 13 mL of A. esculentus , and 24 mL of P. guajava ). Moreover, the improved product shows antibacterial activity against the bacteria Lactobacillus acidophilus and Streptococcus mutans , which cause tooth decay.…”
Section: Fortified Chocolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, Şahin‐Cebeci (2019) showed that incorporating 2% (w/w) Spirulina in homemade chocolate had nearly four times the protein content of commercial baby foods, and it could meet the required daily intake of essential amino acids, histidine, and arginine for infants and children. Raja et al (2021) increased the amount of physiologically active substances in chocolate by including Centella asiatica , Abelmoschus esculentus , and Psidium guajava in the formula compared to conventional chocolates, the optimized product contained more calcium (67.8 mg), iron (2.34 mg), and sodium (355 mg) per 100 g (13 mL of C. asiatica , 13 mL of A. esculentus , and 24 mL of P. guajava ). Moreover, the improved product shows antibacterial activity against the bacteria Lactobacillus acidophilus and Streptococcus mutans , which cause tooth decay.…”
Section: Fortified Chocolatesmentioning
confidence: 99%
“…It appears that the use of oleogels made with bioactive substances that have lower saturated and transfatty acid levels in the chocolate industry could play a significant role in enhancing consumer health.Spirulina, a microalgae with great protein (nearly 70% of the biomass) and amino acid content, is an innovative and promising substance for novel chocolate formulation. Hence, Şahin-Cebeci (2019) showed that incorporating 2% (w/w) Spirulina in homemade chocolate had nearly four times the protein content of commercial baby foods, and it could meet the required daily intake of essential amino acids, histidine, and arginine for infants and children Raja et al (2021). increased the amount of physiologically active substances in chocolate by including Centella asiatica, Abelmoschus esculentus, and Psidium guajava in the formula compared to conventional chocolates, the optimized product contained more calcium (67.8 mg), iron (2.34 mg), and sodium (355 mg) per 100 g (13 mL of C. asiatica, 13 mL of A. esculentus, and 24 mL of P. guajava).…”
mentioning
confidence: 99%